Acoustic method Temperature and velocity fields in the furnace Co-measurement method study - Li, Yanqin (Transactions on Computer Science and Intelligent Systems Research, 2024)
The combustion power field and velocity field of power station boiler chamber have a direct impact on the boiler operation economy and reliability, and the power field in the furnace must be measured collaboratively. However, the thermal conditions of the power field environment is harsh, the traditional method can not be effectively detected, non-contact acoustic wave method can be taken to measure, high precision, simple methods, real-time detection can be realized. Based on this, this paper briefly discusses the acoustic wave method furnace temperature field and velocity field measurement principle, the temperature field and velocity field model construction, acoustic wave trajectory to be analyzed, targeted reconstruction of the temperature field and velocity field, to carry out experimental testing, improve the measurement efficiency and quality, in order to provide reference for related workers.